Entre gouvernance locale et institutionnalisation des territoires - Vincent Andreu-Boussut; Claire Choblet (VertigO)
For less than a decade, the European Commission has been working towards the promotion of the concept of Integrated Coastal Zone Management (ICZM), which aims at identifying coherent coastal territories where all the various stakes and stakeholders could be taken into account. In France most particularly, this definition both reminds of and questions the pattern of the Natural Regional Parks (PNR), whose creation by the DATAR dates back to 1967 – its purpose was to articulate the issues of environmental conservation and socio-economic development in shrinking territories. This management tool quickly became a real reference for local development and PNRs gradually emerged on coveted territories like the French coastal zone where numerous conflicts are generated between various forms of economic development and the increased need to preserve natural spaces and resources. Through the study of two examples, namely the Narbonnaise PNR on the Mediterranean coast, created at the end of 2003, and the current project of the Morbihan Gulf in Britanny, this article is intended to identify the strengths and weaknesses of such institutions in the implementation of the ICZM. In spite of theoretical similarities in the processes of creation, the history of these two projects is quite different, which cannot but reveal the impact of local stakeholders’ strategies into a system mainly promoted and led by the State. So, this article examines the mechanisms collective action gives rise to, as well as the articulation between the stakeholders’ strategies and social practices, not to mention the legitimacy of people’s intervention. Beyond this question, what is at stake is the very relevance – or the limits – of PNRs as efficient tools for the coastal sustainable development.